2020
DOI: 10.3389/fphar.2020.00433
|View full text |Cite
|
Sign up to set email alerts
|

Risks of Sulpiride-Induced Parkinsonism in Peptic Ulcer and Gastroesophageal Reflux Disease Patients in Taiwan: A Nationwide Population-Based Study

Abstract: Background: Sulpiride is a highly selective dopamine D2 receptor antagonist and is commonly used in psychiatric disorders, Tourette syndrome, peptic ulcer disease (PUD), and gastroesophageal reflux disease (GERD). However, sulpiride has been recognized as a potential cause of drug-induced parkinsonism (DIP) for a long time. In this study, we aimed to focus on analysis of sulpiride-induced parkinsonism (SIP) in PUD and GERD patients based on a nationwide population. Methods: Data were obtained from the Taiwan's… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 34 publications
(41 reference statements)
0
6
0
Order By: Relevance
“…Promotes gastric peristalsis and emptying, in addition to inhibiting reflux of gastric contents after meals; can increase pressure on the lower oesophageal sphincter [41,90,91] Sulpiride DRD2 inhibitor Can reduce the secretion of gastric protein and gastric acid and inhibit the development of gastric ulcers [18,35,42] Cisapride DRD2 antagonist Can increase the release of acetylcholine in the intestinal plexus to stimulate the movement of the lower oesophagus, stomach, and small intestine [19] SKF 38393 DRD1 inhibitor Inhibits the development of gastroduodenal ulcers [35] Metoclopramide DR antagonist Increases gastric emptying while also exerting antiemetic effects [39,40] Domperidone DRD2 antagonist Inhibits intestinal motility, regulates sodium absorption and mucosal blood flow, and has a protective effect against gastroduodenal ulcers [47,48] Calilazine DRD3 antagonist Can inhibit multiple drug resistance and make colon and lung cancer cells sensitive to antitumor drugs [52] Pimozite DRD2 antagonist Inhibits the growth and metastasis of colorectal cancer (CRC) [53] Thioridazine DRD2 antagonist Inhibits the growth of gastric cancer cells to exert antitumor effects; ameliorates hepatocellular carcinoma to possibly reduce the risk of tumour metastasis [54,83] Quinpirol DRD2 agonist Reduces the permeability of blood vessels and prevents excessive leakage of blood vessels, thereby decreasing the severity of UC [56,57,62] Bromocriptine…”
Section: Domperidone Drd2 Antagonistmentioning
confidence: 99%
See 1 more Smart Citation
“…Promotes gastric peristalsis and emptying, in addition to inhibiting reflux of gastric contents after meals; can increase pressure on the lower oesophageal sphincter [41,90,91] Sulpiride DRD2 inhibitor Can reduce the secretion of gastric protein and gastric acid and inhibit the development of gastric ulcers [18,35,42] Cisapride DRD2 antagonist Can increase the release of acetylcholine in the intestinal plexus to stimulate the movement of the lower oesophagus, stomach, and small intestine [19] SKF 38393 DRD1 inhibitor Inhibits the development of gastroduodenal ulcers [35] Metoclopramide DR antagonist Increases gastric emptying while also exerting antiemetic effects [39,40] Domperidone DRD2 antagonist Inhibits intestinal motility, regulates sodium absorption and mucosal blood flow, and has a protective effect against gastroduodenal ulcers [47,48] Calilazine DRD3 antagonist Can inhibit multiple drug resistance and make colon and lung cancer cells sensitive to antitumor drugs [52] Pimozite DRD2 antagonist Inhibits the growth and metastasis of colorectal cancer (CRC) [53] Thioridazine DRD2 antagonist Inhibits the growth of gastric cancer cells to exert antitumor effects; ameliorates hepatocellular carcinoma to possibly reduce the risk of tumour metastasis [54,83] Quinpirol DRD2 agonist Reduces the permeability of blood vessels and prevents excessive leakage of blood vessels, thereby decreasing the severity of UC [56,57,62] Bromocriptine…”
Section: Domperidone Drd2 Antagonistmentioning
confidence: 99%
“…Therefore, domperidone is a rational option for the treatment of gastro oesophageal reflux disease 16,17 . Sulpiride is a highly selective DRD2 antagonist mainly used for the treatment of PUD and GERD 18 . Sisapride is a DRD2 antagonist.…”
Section: Roles Of Dopamine and Dopamine Receptors In Oesophageal Dise...mentioning
confidence: 99%
“…A study in Korea found an incidence rate of 8.69/100,000 over a three-year period [28], with incidence increasing with age up until the age bracket 75-79y (higher in women than men), and decreasing slightly from age 80. Finally, in a study from Taiwan using data from the National Health Insurance Research Database over the period 2000-2012, the incidence of DIP was found to be of 762.2/100,000 in patients who had taken sulpiride (a highly selective D2R antagonist) for the management of gastro-oesophageal reflux disorder, compared to those who were not treated with this drug [31]. When looking at age groups, the Olmsted study showed an increasing incidence of DIP from age 60, with the highest incidence in women in the age group 80-89 [14]: 31.8/100,000/year in men and 60.8/100,000 in women.…”
Section: Epidemiology and Risk Factorsmentioning
confidence: 99%
“…Most studies report that increasing age (for both sexes) and female gender are more frequently associated with incidence and prevalence of DIP [8][9][10]14,16,17,23,[25][26][27][28]31,33]. However, the vast majority of these studies include all drug groups associated with DIP, hence it is difficult to ascertain the precise prevalence and incidence of AIP.…”
Section: Epidemiology and Risk Factorsmentioning
confidence: 99%
See 1 more Smart Citation